Christianity Facing the Ageing of Global Population - Sanecka, Anna (Journal of Education Culture and Society, 2020)
The ageing population is a great challenge for the whole world including churches, Christian communities, Christian families and the so-called “Christian countries”. The respect and support for elderly people is almost a common rule of social life in developed countries regardless of religious views. But in the Christian world this obligation has very strong religious justification – obligation enshrined in the Commandments of Old (the fourth/fifth Commandment) and New (the second one of The Greatest Commandments of Love) Testaments. Therefore between the Christianity – understood as a set of different communities sharing their beliefs in Jesus Christ – and aging population there are many very different connections including among others: honour and respect, privilege, obligations, giving – receiving relations, duty, charity, solidarity, dependency. They are present both in the teaching and the practice of different Christian communities starting with Churches, through NGOs and Christian societies, ending with Christian families. The paper shows some of these connections. It also tries – based on a case of Poland – to answer the question whether the Christianity is ready to face the aging of global population.